3D pharmacophore based virtual screening of T-type calcium channel blockers - Doddareddy, Munikumar Reddy; Choo, Hyunah; Cho, Yong Seo; Rhim, Hyewhon; Koh, Hun Yeong; Lee, Jung-Ha; Jeong, Seong-Woo; Pae, Ae Nim (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Virtual screening of the commercial databases was done by using a three dimensional pharmacophore previously developed for T-type calcium channel blockers using CATALYST (TM) program. Biological evaluation of 25 selected virtual hits resulted in the discovery of a highly potent compound VH04 with IC50 value of 0.10 mu M, eight times as potent as the known selective T-type calcium channel blocker, mibefradil. Search for similar compounds yielded several hits with micro-molar IC50 values and high T-type calcium channel selectivity. Based on the structure of the virtual hits, small molecule libraries with novel scaffolds were designed, synthesis and biological evaluation of which are currently in progress. This result shows a successful example of ligand based drug discovery of potent T-type calcium channel blockers. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: STABLE ANGINA; MIBEFRADIL